Development of Mathematics Learning Materials Based on Pancasila - Friska Situngkir; Hidayatul Mazidah Harahap; Sondang Noverica Panjaitan (JNPM (Jurnal Nasional Pendidikan Matematika), 2025)
This research aims to develop mathematics learning tools based on Pancasila values to support students' character building and mathematical competence improvement. The main problem raised is the lack of integration between mathematics learning and character education, especially the noble values of Pancasila. The method used in this research is Research and Development (R&D) with a development model that refers to the simplified Borg and Gall steps. The tools developed include Learning Implementation Plan (RPP), Learner Worksheet (LKPD), and assessment instruments. Pancasila values are integrated into learning activities through contextual, collaborative, and problem-based approaches. The results of the expert validation test showed that the tools developed were in the very valid category, while the results of the limited trial showed that the tools were able to increase student involvement and foster positive attitudes such as responsibility, cooperation, and justice. Thus, this Pancasila-based mathematics learning tool is considered feasible to be used and further developed in the context of character education in schools.